2021
DOI: 10.1177/21925682211034500
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation Techniques to Prevent Proximal Junctional Kyphosis and Proximal Junctional Failure in Adult Spinal Deformity Correction: A Systematic Review of Clinical Studies

Abstract: Study Design: Systematic review. Objectives: To summarize the results of clinical studies investigating spinal instrumentation techniques aiming to reduce the postoperative incidence of proximal junctional kyphosis (PJK) and/or failure (PJF) in adult spinal deformity (ASD) patients. Methods: EMBASE and Medline® were searched for articles dating from January 2000 onward. Data was extracted by 2 independent authors and methodological quality was assessed using ROBINS-I. Results: 18 retrospective- and prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Multiple in vivo studies have gone on to use this surgical technique in long-segment fusions. [15][16][17][18][19][20][21][22] In our literature search, we found 4 retrospective studies, 15,17,19,20 2 prospective studies, 16,18 and 2 systematic reviews 21,22 regarding PVP in the prevention of adjacent segment disease. Of these, Raman et al 18 had the largest cohort of patients treated with cement augmentation at the UIV and rostral adjacent vertebra (UIV + 1) with a total of 39 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple in vivo studies have gone on to use this surgical technique in long-segment fusions. [15][16][17][18][19][20][21][22] In our literature search, we found 4 retrospective studies, 15,17,19,20 2 prospective studies, 16,18 and 2 systematic reviews 21,22 regarding PVP in the prevention of adjacent segment disease. Of these, Raman et al 18 had the largest cohort of patients treated with cement augmentation at the UIV and rostral adjacent vertebra (UIV + 1) with a total of 39 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reported modalities used to help prevent PJK/ PJF, such as 2-level prophylactic vertebroplasty (PVP) at the UIV and UIV + 1. [15][16][17][18][19][20][21][22] In this study, we report the largest current series of prophylactic cement augmentation with UIV + 1 vertebroplasty and an updated literature review. This was a cohort analysis and not a case-control study.…”
Section: Objectivesmentioning
confidence: 99%
“…PJK and PJF are common mechanical complications following ASD surgery and have been extensively studied and reviewed. [112][113][114] The incidence of PJK following ASD surgery has been investigated in several studies and review series, and is estimated to occur in 20% to 50% of cases [114][115][116][117][118] (Table 4). A recent metaanalysis of 2215 unique patients across 14 studies found that the primary risk factors for PJK included: older age, long-segment fusion to the rigid spine (sacrum/ilium), a large thoracic kyphotic angle, osteoporosis, and sagittal malalignment.…”
Section: Pjk/failurementioning
confidence: 99%
“…Accordingly, several investigators have focused on risk-reduction techniques to prevent PJK, which generally fall into three categories: (1) implementing tailored surgical plans, (2) instrumentation techniques, and (3) augmentation and preservation of the posterior tension band. 112,113,121,127 First, several studies have suggested that excess LL in ASD correction predisposes to higher PJK risks. 119 Ageappropriate correction of sagittal malalignment has been proposed as a means of reducing PJK risk.…”
Section: Pjk/failurementioning
confidence: 99%
See 1 more Smart Citation